2020
DOI: 10.24996/ijs.2020.61.8.8
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Different Susceptibility Test Methods to Evaluate the Antibacterial Activity of Olibanum and Alum Against the "Red Complex" Periodontal Pathogens

Abstract: Testing the sensitivity of periodontal pathogens requires the selection of an easier and more reliable method to be used with such anaerobic bacteria that need a long period of time for growth. Natural materials are a new era of antibacterial agents to control periodontal infections. The aims of the current study were to test the antibacterial activity of two natural agents, namely olibanum and alum, against three types of red complex periodontal pathogens and compare the application of agar diffusion and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…Al-Hamdoni and Al-Rawi [30] reported that frankincense extract exhibited antibacterial activity against the red complex periodontal pathogens isolated from patients in Mosul, Iraq with MIC value of 2.4 mg/mL. The difference between the MIC values reported in the current study and that of Al-Hamdoni and Al-Rawi [16,30] could be explained by the finding reported by Di Stefano et al [40]. They noticed that frankincense essential oils derived from three different Boswellia sacra cultivars had different MIC values against Staphylococcus aureus, Pseudomonas aeruginosa, and Propionibacterium acnes standard isolates.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Al-Hamdoni and Al-Rawi [30] reported that frankincense extract exhibited antibacterial activity against the red complex periodontal pathogens isolated from patients in Mosul, Iraq with MIC value of 2.4 mg/mL. The difference between the MIC values reported in the current study and that of Al-Hamdoni and Al-Rawi [16,30] could be explained by the finding reported by Di Stefano et al [40]. They noticed that frankincense essential oils derived from three different Boswellia sacra cultivars had different MIC values against Staphylococcus aureus, Pseudomonas aeruginosa, and Propionibacterium acnes standard isolates.…”
Section: Discussioncontrasting
confidence: 53%
“…Hence, the need to use local antiseptics or systemic antibiotic therapy is recommended to improve the treatment outcome [15]. Systemic antibiotics are of great benefit as they reach the periodontal tissues via blood to suppress periodontal pathogens [16]. However, the emergence of antibiotic-resistant bacteria has made infectious diseases more difficult to treat [17].…”
Section: Introductionmentioning
confidence: 99%